MIFTAHUL JANNAH ORPHANAGE HAS A HAPPY RAMADAN WITH GREAT CHILDREN - Likdanawati; Hamdiah; Jumadiah; Risna Dewi; M. Subhan; Sutriani (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
This article discusses a Ramadan community-service program conducted at Miftahul Jannah Orphanage as a child-centered initiative that integrates Islamic philanthropy, psychosocial support, educational engagement, and joyful worship experiences. The program was developed to respond to the need for meaningful social support among children in alternative care, where material assistance alone is insufficient to strengthen emotional security, dignity, and social connectedness. Using a descriptive qualitative community-service approach, the activity was organized through preliminary coordination, needs identification, participatory preparation, Ramadan sharing, educational games, reflective dialogue, iftar gathering, and post-activity evaluation. Data were interpreted from field observation, documentation, volunteer reflection, and informal feedback from caregivers and children. The results show that a well-structured Ramadan activity can create a warm social atmosphere, support children’s confidence, encourage positive peer interaction, and improve volunteer awareness of ethical service. The study contributes a practical model for faith-based community engagement that emphasizes accountability, child protection, educational value, and sustainable relationships. The program demonstrates that Ramadan social service should not be limited to charity distribution, but should also build inclusive spaces where children are recognized as capable, valued, and great individuals.